METAPHYSICS OF THE INFOSPHERE AND ETHICAL CHALLENGES OF GENERATIVE AI: A NEW ETHICAL LANDSCAPE - Shorina, Tetiana (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
The technologies of the Third and Fourth Industrial Revolutions not only reshape the material landscape of society but are also increasingly acknowledged as key agents in constructing a new social model. However, the significant challenges accompanying the global information society-namely, access to information for all and the future freedom of expression of opinion-reveal the culturally constrained and socially alienated character of this emerging model. The aim and tasks. The aim is to analyze the metaphysics of the infosphere and identify ethical challenges associated with generative artificial intelligence (AI). The tasks include: defining the infosphere as a new ontological reality, drawing on the philosophical work of Luciano Floridi; outlining its connection to the technological developments of Industry 4.0, with reference to Klaus Schwab’s analysis; examining the main ethical challenges posed by generative AI, as well as the ethical standards proposed for its regulation; and synthesizing philosophical and humanistic ideals-particularly those presented in UNESCO documents – in order to evaluate the limitations of the current information society paradigm. Research methods. The study applies the conceptual principles of social philosophy, philosophy of culture, and information ethics, alongside general scientific principles such as historicism and systematics, and logical methods of substantiation and argumentation. The comparative method, discursive analysis, and an interdisciplinary approach are also employed. Research results. The current information society paradigm, when examined through the lens of philosophical and humanistic ideals - as highlighted in UNESCO materials - reveals significant cultural and ethical limitations. These findings indicate that generative AI and digital transformation are not merely technological advancements; rather, they represent a profound shift in the construction and experience of reality. Discussion. The emphasis on humanistic values calls for a reorientation from a model solely focused on data and automation towards "knowledge societies", where information is transformed into meaningful insights through education, cultural exchange, and ethical reflection. This transition is essential to ensure that technological progress is not detached from the core human values that sustain societal well-being, fostering a more inclusive and critically engaged digital future. Conclusions. Rethinking reality in information terms requires the creation of a new metaphysics that is designed to comprehend the nature of data, knowledge, and the moral principles of managing the digital environment. In particular, its task is to find a balance between a new type of computer autonomy and human autonomy. In its prognosis, the philosophy of information should avoid two extremes: apocalyptic predictions and utopian views on social and environmental well-being. Although there are many serious challenges related to the use of generative AI, it conceals the potential for building a more just and sustainable world. The developed ethical norms, focused on transparency, responsibility, and justice, resonate with the paradigm of “knowledge societies” and align with the humanistic values promoted by UNESCO.